2006
DOI: 10.1111/j.1365-2648.2006.03836.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of nurse‐led brief alcohol intervention: a cluster randomized controlled trial

Abstract: The new COPD-GRIP (Chronic Obstructive Pulmonary Disease-Guidance, Research on Illness Perception) intervention translates evidence regarding illness perceptions and health-related quality of life (HRQoL) into a nurse intervention to guide COPD patients and to improve health outcomes. It describes how to assess and discuss illness perceptions in a structured way. This study aimed to assess the effectiveness of the intervention in primary care. A cluster randomised controlled trial was conducted within 30 gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
85
0
10

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(97 citation statements)
references
References 48 publications
2
85
0
10
Order By: Relevance
“…Over 90 % of the \1 scores in the sample included some problem with anxiety/depression, and over 50 % indicated moderate anxiety/depression and no other problems. These findings are consistent with previous research, where mental health problems have been shown to dominate QoL in studies using both the EQ-5D [16,19,23] and other QoL tools [38,[42][43][44][45][46][47].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Over 90 % of the \1 scores in the sample included some problem with anxiety/depression, and over 50 % indicated moderate anxiety/depression and no other problems. These findings are consistent with previous research, where mental health problems have been shown to dominate QoL in studies using both the EQ-5D [16,19,23] and other QoL tools [38,[42][43][44][45][46][47].…”
Section: Discussionsupporting
confidence: 92%
“…Studies using other generic HRQoL measures in nontreatment populations have also found a lack of significant association between alcohol use and summary HRQoL scores [46,53], or sensitivity to changes in alcohol consumption over time [38,43].…”
Section: Discussionmentioning
confidence: 99%
“…However, one recent cluster, randomized controlled trial (Lock et al, 2006) assessed the effectiveness of a nurse-led brief (5 to 10-minute) alcohol intervention in primary health care in the U.K. Results indicated that this intervention was no better than standard advice.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review suggests that the literature on the cost of SBI is more developed than that on the cost of the SBIRT program [13]. The review also indicates that the estimates of SBI costs vary substantially [14][15][16][17][18][19][20][21][22][23][24][25]. Some of the cost variation is probably attributable to differences in staffing (e.g.…”
Section: Introductionmentioning
confidence: 99%